The Effects of Participatory Nursing Model on Nurses’ Perception for Professional Value and Decision for Advance Care Planning of Patient with Risk of Stroke - Mamad, Zainoon; Apiruknapanond, Panta; Laoopugsin, Suwannee (Journal of health and health management, 2024)
This semi-experimental research The objective is to study the results of using participatory nursing models to recognize the professional value of professional nurses. And the advance planning decision of patients with stroke risk The sample is divided into 2 groups, namely the professional nursing group that operatesIn the 25 gymnast patients and the user group, the control group is a group in which 20 users receive traditional nursing and the trial group is a group in which users are nursing using participatory nursing forms 20 Research tools have 2 parts. Part 1 is an experimental tool. And the tools used to direct the experiment are as follows: 1.1 participatory nursing model By using the concept of participatory management principles of Susshkin And operated byParticipation of professional nurses, internal medicine ward, 1.2 tools used to supervise experiments, including 1) knowledge tests About stroke and advance planning decisions of professional nurses Before and after the development of participatory nursing models and 2) Knowledge test In practice when having a stroke Of service users After the development of a participatory nursing model, Part 2, the tools used to gather information are as follows: 2.1 Yon Eunja’s Nursing Professional Recognition Questionnaire and Faculty (Yeun et al., 2005) And 2.2 knowledge evaluation model And pre-planned decisions developed by the researcher And the patient’s advance decision record in writing The statistics used in the research are the average percentage, standard deviation, and comparison of knowledge and judgment.The pre-planned mind of the user group during the period after receiving the same nursing and after using the participatory nursing model by Mann-Whitney U statistics. The results show that 1. After using the participatory nursing model Nurses have a higher professional value recognition of professional nurses than before using the participatory nursing model. When considered on a side basis, found that After using the participatory nursing model Nurses that are sample groups have a high level of professional value recognition.More than before, the use of 3-sided participatory nursing models is 1) Professional appreciation 2) Social and cultural awareness 3) Role in nursing services As for the perceived professional value that is not higher, there are 2 areas 1) Nursing professionalism and 2) Nursing initiatives and 2. Knowledge and advance planning decisions of service users receiving participatory nursing forms Higher than those receiving traditional nursing. Statistically significant at level .05.